La tyrannie paysagère - Paquet, Suzanne (Ciel variable)

(untitled) (Les Productions Ciel variable, 2006)
Abstract Since the nineteenth century, the rule for collecting photographic "landscapes" has allowed a certain "tyranny of the landscape" to endure and proliferate, making it so that the capturing of places and territories of the world could no longer be admitted without the mediation of photography. With a few observations on current art-photography practices, offering a short inventory of current landscape and geography themes, the author proposes that artists need to take a critical look at this phenomenon.